(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد البحث دراسة ميدانية لواقع الخدمات الصحية المقدمة في مشفى الباسل بمحافظة طرطوس وذلك بغية التعرف على نقاط القوة والضعف، ومدى الحاجة إلى إعادة الهندسة الإدارية من أجل مواجهة التحديات المستقبلية للمشافي. ويعتمد البحث على العاملين وعلى المرضى الذين استفادوا من خدمات المشفى بغية الوقوف على حقيقة الوضع الراهن للمشفى، وفي نهاية البحث تم صياغة مجموعة من التوصيات الهادفة إلى تحسين الواقع الصحي في المشفى. This research is a field study of the situation of health services in Bassel Hospital in Tartous governorate in order to identify the strengths and weaknesses, and the need for administrative re-engineering management to meet the future challenges for hospitals. This research depends on the workers and the patients who benefited from the services of the hospital in order to identify the fact of the current status in the hospital, and at the end of the research was to formulate a set of recommendations aimed at improving the health situation in the hospital.